Analysis Of Promotional Strategies And Service Quality On Usage Satisfaction Steam Hjg Car Wash In Pungur District Central Lampung - Helen Chrystina Putri; Vonny Tiara Narundana (Global Leadership Organizational Research in Management, 2024)
With car production increasing every year, the automotive industry has grown rapidly in the modern era. This growth has also led to the development of ancillary service sectors such as auto repair shops, auto shows, sales of vehicle accessories and components, and carwash services. Car wash services, in particular, have become very necessary in this day and age, especially for those who cannot and have limited time to wash their own vehicles at home. As a business in the service sector, it is important to implement effective promotional plans and provide optimal service quality to customers to ensure their satisfaction with the services provided. This research aims to evaluate the effect of promotional strategies and service quality on the satisfaction of HJG Carwash users in Punggur District, Central Lampung, either partially or simultaneously. From a population of 242 people, the research sample was taken from 151 respondents. The research method applied is multiple regression analysis with the IBM SPSS Statistics application. The results prove that promotional strategies do not have a positive impact on user satisfaction, while service quality has a positive impact partially on HJG Carwash user satisfaction. However, simultaneously, the two variables together have a positive and significant impact on HJG Carwash user satisfaction. In this study, 29.5% of the variation in customer satisfaction can be explained by the model used, while the remaining 0.705 cannot be described in this research.